2021
DOI: 10.1007/s12369-020-00715-z
|View full text |Cite
|
Sign up to set email alerts
|

Should I be Introvert or Extrovert? A Pairwise Robot Comparison Assessing the Perception of Personality-Based Social Robot Behaviors

Abstract: with details of the nature of the infringement. We will investigate the claim and if justified, we will take the appropriate steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 55 publications
(73 reference statements)
0
4
0
1
Order By: Relevance
“…Jung also revealed that a person with a shy type of introverted Personality feels very wary around strangers and becomes very nervous in a lesser-known environment. The introverted Personality has difficulty developing social relationships and prefers to communicate personally with friends as well as enjoy any activities that can be done alone or with close friends (Esteban, 2022). An introverted person is calm in nature, prefers to withdraw, and is less friendly.…”
Section: Results and Discussion Understanding Introvert Personalitymentioning
confidence: 99%
“…Jung also revealed that a person with a shy type of introverted Personality feels very wary around strangers and becomes very nervous in a lesser-known environment. The introverted Personality has difficulty developing social relationships and prefers to communicate personally with friends as well as enjoy any activities that can be done alone or with close friends (Esteban, 2022). An introverted person is calm in nature, prefers to withdraw, and is less friendly.…”
Section: Results and Discussion Understanding Introvert Personalitymentioning
confidence: 99%
“…Aspects related to speech, including speech volume, speed, pitch, style, vocabulary, topic selection, feedback, syntax, and backchannel, have been examined. These factors contribute significantly to nonverbal communication, impacting the quality of human-robot conversations by influencing mutual engagement and attentiveness [26,48,59].…”
Section: Types Of Nonverbal Communication Examinedmentioning
confidence: 99%
“…De acuerdo con este principio de «similitudatracción», cuando los participantes trabajan con un robot que muestra un estilo de personalidad que coincide con el suyo, «dominante» o «sumiso», lo consideran más inteligente y convincente, a pesar de que el contenido sea idéntico. Es más, cuando la «personalidad» del robot coincide con la del usuario, es más probable que las personas le den crédito al agente por su éxito y menos probable que le culpen por el fracaso, en comparación a cuando hay un desajuste de personalidad (Esteban et al, 2022).…”
Section: Antropomorfismo Y Categorías Sociales Humanasunclassified